1998
DOI: 10.1111/j.1469-8749.1998.tb15399.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gross motor skills of at‐risk infants: predictive validity of the Alberta Infant Motor Scale

Abstract: The Alberta Infant Motor Scale (AIMS) is a norm-referenced measure of infant gross motor development. The objectives of this study were: (1) to establish the best cut-off scores on the A I M S for predictive purposes, and (2) to compare the predictive abilities of the AMIS with those of the Movement Assessment of Infants (MAI) and the Peabody Developmental'Gross Motor Scale (PDGMS). One hundred and sisty-four infants were assessed at 4 and 8 months adjusted ages on the three measures. A pediatrician assessed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
160
1
21

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(203 citation statements)
references
References 17 publications
5
160
1
21
Order By: Relevance
“…37,[51][52][53][54][55] The authors have established cutoff points in order to classify the child within a risk profile, demonstrating higher sensitivity for the identification in children older than 6 months (Table 3). 50 These findings have been checked in other studies, and the results confirmed high sensitivity rate, but the best specificity and accuracy rates were associated with results with a percentile ≤ 5. addition to the necessity of further studies to define the clinical importance of the assessment. [59][60][61][62][63] Another issue that has been pointed out by some researchers is related to the differences found in the mean of the results for foreign popula-…”
Section: Summary Of the Findingssupporting
confidence: 65%
See 1 more Smart Citation
“…37,[51][52][53][54][55] The authors have established cutoff points in order to classify the child within a risk profile, demonstrating higher sensitivity for the identification in children older than 6 months (Table 3). 50 These findings have been checked in other studies, and the results confirmed high sensitivity rate, but the best specificity and accuracy rates were associated with results with a percentile ≤ 5. addition to the necessity of further studies to define the clinical importance of the assessment. [59][60][61][62][63] Another issue that has been pointed out by some researchers is related to the differences found in the mean of the results for foreign popula-…”
Section: Summary Of the Findingssupporting
confidence: 65%
“…39,43,44,46 from other instruments previously designed, the AIMS was created to fulfill the necessity of pediatric therapists regarding the selection and follow-up of the sequential motor development. 50 The assessment is performed based on the free observation of the child in four positions: supine (nine items), prone (21 items), sitting (12 items) and standing (16 items). The test assesses how long the child keeps the position, the correlation, sensitivity and specificity rates (Table 2).…”
Section: Summary Of the Findingsmentioning
confidence: 99%
“…This demonstrated a high degree of congruence between the AIMS scores and those of the BSID motor scale (r = 0.97), and also between the AIMS scores and those from the PDMS (r = 0.99). 14 The predictive capacity of the AIMS varies depending on the age at which the evaluation is made, 17 and percentiles below 10 at 4 months of age and below five at 8 months of age can be considered valid and reliable indicators of motor development delay or abnormality. 17 The AIMS has been used in several different studies in Brazil, 18 and is considered useful and practical for evaluation of the motor development of premature infants within follow-up programs run by the Brazilian public health system.…”
Section: Introductionmentioning
confidence: 99%
“…14 The predictive capacity of the AIMS varies depending on the age at which the evaluation is made, 17 and percentiles below 10 at 4 months of age and below five at 8 months of age can be considered valid and reliable indicators of motor development delay or abnormality. 17 The AIMS has been used in several different studies in Brazil, 18 and is considered useful and practical for evaluation of the motor development of premature infants within follow-up programs run by the Brazilian public health system. However, it still remains necessary to verify its psychometric properties, since satisfactory levels of instrument validity and reliability are not guaranteed when instruments are used with populations that are culturally distinct from those with which they were developed.…”
Section: Introductionmentioning
confidence: 99%
“…Diante de tais resultados, acredita-se que nos primeiros meses de vida a correção da idade gestacional se faz ainda mais necessária para que a criança demonstre desenvolvimento motor adequado, já que pesquisas tem observado uma tendência de melhora no desempenho motor de lactentes pré-termo com o avançar da idade 11,18,23,24 . Pesquisadores propõem que a correção se de até os dois anos de idade e alinhando-se aos achados do presente estudo confirma-se a importância de considerar a idade corrigida em crianças com idade até 18 meses 25 .…”
Section: Discussionunclassified